Three cases of tufting enteropathy and review of literature - Noyan, Aslı; Gümüş, Ersin; Hızarcıoğlu Gülşen, Hayriye; Demir, Hülya; Orhan, Diclehan (The Turkish Journal of Pediatrics, 2026)
Background. Congenital tufting enteropathy (CTE) is a rare autosomal recessive enteropathy characterized by intractable watery diarrhea independent of feeding, electrolyte imbalances and severe malnutrition. The aim of this case series is to highlight the characteristic yet easily overlooked histological features of tufting enteropathy, especially in cases where initial biopsies may be reported as nonspecific, and to emphasize the importance of clinicopathological correlation and genetic confirmation. Case Presentation. Here we report 3 patients with tufting enteropathy who have the characteristic histological findings and demonstrate the use of EpCAM (epithelial cell adhesion molecule) immunohistochemistry. One case was diagnosed by histopathological examination, while the other 2 were diagnosed by genetic analysis. Conclusions. These cases illustrate that the histopathological features of CTE, though subtle, are usually present from the outset and can be recognized when specifically sought. Correlation with genetic testing is essential for confirmation, but increased awareness of the characteristic epithelial tufts may reduce diagnostic delay and improve patient management.